Multiple Survival Outcome Prediction of Glioblastoma Patients Based on Multiparametric MRI - Wang, Bin; Zhang, Shan; Wu, Xubin; Li, Ying; Yan, Yueming; Liu, Lili; Xiang, Jie; Li, Dandan; Yan, Ting (Frontiers in Oncology, 2021)
Purpose: Construction of radiomics models for the individualized estimation of multiple survival stratification in glioblastoma (GBM) patients using the multiregional information extracted from multiparametric MRI, which could facilitate clinical decision-making for GBM patients. Materials and Methods: A total of 134 eligible GBM patients were selected from the Cancer Genome Atlas. These patients were separated into the long-term and the short-term survival groups according to the median of individual survival indicators: overall survival (OS), progression free survival (PFS) and disease-specific survival (DSS). Then the patients were divided into a training set and a validation set in a ratio of 2:1. Radiomics features (n= 5152) were extracted from multiple regions of the GBM using multiparametric MRI. Then, radiomics signatures which related to the three survival indicators were respectively constructed using the analysis of variance (ANOVA) and the least absolute shrinkage and selection operator (LASSO) regression for each patient in the training set. Based on a Cox proportional hazards model, the radiomics model was further constructed by combining the signature and clinical risk factors. Results: The constructed radiomics model showed a promising discrimination ability to differentiate in the training set and validation set of GBM patients with survival indicators of OS, PFS, and DSS. Both the four MRI modalities and five tumor subregions have different effects on the three survival indicators of glioblastoma. The favorable calibration and decision curve analysis indicated the clinical decision value of radiomics model. The performance of models of the three survival indicators was different but excellent, the best model achieved C indexes of 0.725, 0.677 and 0.724 respectively in the validation set. Conclusion: Our results show that the proposed radiomics models have favorable predictive accuracy on three survival indicators, and can provide individualized probabilities of survival stratification for GBM patients by using multi-parametric and multi-regional MRI features.